Synthesis of fluoroalkenes and fluoroenynes via cross-coupling reactions using novel multihalogenated vinyl ethers - Karuo, Yukiko; Hirata, Keita; Tarui, Atsushi; Sato, Kazuyuki; Kawai, Kentaro; Omote, Masaaki (Beilstein Journal of Organic Chemistry, 2024)
In this study, we develop the synthesis methods of fluoroalkenes and fluoroenynes via Suzuki–Miyaura and Sonogashira cross-coupling reactions using novel multihalogenated fluorovinyl ethers, which are easily prepared from the reaction between phenols and 2-bromo-2-chloro-1,1,1-trifluoroethane (halothane). These reactions make use of the unique structure of multihalogenated fluorovinyl ethers, which contains a reactive bromine atom, to afford a series of fluoroalkenes and fluoroenynes in moderate to high yields.
Keywords: fluoroalkenes; fluoroenynes; multihalogenated vinyl ethers; Suzuki–Miyaura cross-coupling reactions; Sonogashira cross-coupling reactions